Digital Marketing Strategy in Building Brand Awareness on Instagram of PT Skinplay Labs Indonesia - Zhevio Aufa Amanu; Abung Supama Wijaya (Sinergi International Journal of Communication Sciences, 2026)
The rapid growth of Indonesia’s digital ecosystem and the expanding skincare industry have positioned Instagram as a key platform for brand development and consumer engagement. While many studies evaluate digital marketing effectiveness through quantitative indicators, limited research explores how marketing teams qualitatively conceptualize and execute strategies to build brand awareness. This study addresses that gap by examining the digital marketing practices of PT Skinplay Labs Indonesia (Skinplay), a local skincare brand targeting Generation Z consumers. Using a qualitative case study approach, this research collected data through participatory observation during a five-month internship, in-depth interviews with the marketing team, and analysis of content strategy documents, Instagram analytics, and campaign archives. The findings show that Skinplay applies an agile content framework supported by trend monitoring, social listening, and structured planning cycles. The brand emphasizes meaningful metrics, such as Save Rate and community conversion, over vanity metrics, reflecting a shift toward long-term brand-building priorities. One of the most notable results emerged from the “PLAYDATE Vol. 1 – Mission: Skinpossible” campaign, which integrated online and offline activation and produced a 62% increase in impressions from non-followers. This outcome indicates a substantial rise in exposure beyond the existing audience. Overall, the study concludes that Skinplay’s combination of gamification, emotional storytelling, and community-based engagement effectively strengthens brand awareness and enhances competitive positioning within Indonesia’s saturated skincare market.